Drill Methods in Sepak Takraw Learning for Middle School Students: A Study of Sepak Sila Ability - Asri A; Adil, Ahmad; Fahrizal, Fahrizal; Suwardi, Suwardi; Hudain, Muh. Adnan (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study aims to determine the improvement of sepak sila skills through the drill method in sepak takraw learning in junior high school students. This study uses an approach based on classroom action research. The sample in this study was students of Class VIII of Public Middle School Satu Atap Iwur Pegunungan Bintang, with a sample used of 32 students. The sampling technique used was total sampling. Qualitative data analysis used qualitative descriptive techniques to interpret the results of observations about the learning process. The results showed that in the first cycle of learning Sepak Takraw Sepak Sila using the drill method, the passing rate for all students was 66.67%. In the affective aspect, student motivation to participate in learning still needs to be improved, especially in the early meetings. Discipline and accuracy in performing sepak sila using the drill method still need improvement. While the average completeness value of all students was 93.75% in cycle II, only 7.34% of students had not achieved completeness. However, the learning process encountered several obstacles. In the cognitive aspect, students still have difficulty in working on questions and lack focus when working on assignments, which causes the final grade to be less than optimal. It can be concluded that there is an increase in sepak sila skills by using the drill method in sepak takraw learning among class VIII students of Public Middle School.